Implementasi Model Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Belajar IPA - Iswantari, Indah (Jurnal Paedagogy, 2021)
The purpose of this study is to improve science learning outcomes through the implementation of project-based learning models. The research method used is classroom action research. The number of subjects in this study were 21 students. The research instrument used was a learning outcome test. Meanwhile, the technical analysis of the data in this study used qualitative and quantitative descriptive techniques. The results of this study indicate that the application of a project-based learning model can improve science learning outcomes in class 7.2 students of SMPN 2 Kayangan for the 2020/2021 school year. The learning outcomes of students before the implementation of project-based learning (cycle I) were very low, where the classical completeness score was only 33.3%. After taking action by applying the project-based learning model in cycle II, the classical completeness score was 90.5% where 19 students scored above the KKM.